First report of an outbreak of “Q” fever IN an abattoir from Argentina - Cardillo, Natalia Marina; Bastos, Reginaldo; García, Araceli; Pérez, Rosendo; García, Ezequiel; Lloveras, Susana; Suarez, Carlos (Wiley, 2023)
In late October 2021, one of the veterinarians and the occupational physician of a bovine and swine abattoir from Entre Ríos Province, Argentina were alerted about workers with atypical pneumonia symptoms, raising suspicious of a possible Q fever outbreak. An outbreak epidemiological investigation was carried out. Analysis was based on the description of the study population, according to gender, age, symptoms, and position within the abattoir, as well as on outbreak epidemic curve and its probable origin. Cases of Q fever in the workers were confirmed by serology. Measurements of the association between the evaluated variables and the risk of exposure were investigated and calculated as attack rates. The outbreak occurred between October and November 2021, symptomatically affecting 11 workers, out of a total exposed population of 49 individuals. The index case was a 33-year-old male who started with symptoms on 27 October 2021, and the outbreak extended for at least 17 days. Workers in the clean zone of the slaughter floor had a 4.68 times higher risk of contracting Q fever than people located in other areas. Importantly, two pregnant cows were slaughtered a few days before the outbreak began, which could have been the origin of the outbreak. The present study demonstrates the urgent need to consider Q fever when diagnosing abortive diseases of ruminants in Argentina, as well as in zoonotic disease epidemiological surveillance to inform all actors of the health system.